Ethnographic Study: Sasak Culture In The Perspective Of Ethnomathematics - Ni Wayan Parwati Septiani; Ari Irawan; Rayung Wulan (Urogram Studi Pendidikan Matematika, Universitas IVET, 2023)
The aim of this study is to discover the mathematical aspect that found in Sasak tribe as shown by the architecture, customs and culture that define Sasak tribe. This study was conducted using ethnographic studies and descriptive qualitative analysis. This study focuses both tangible and intangible aspects of sasak tribe culture which represent sasaknese characteristics. Data was collected using interviews, observations and documentation techniques. The data analysis methodology was conducted utilizing a triangulation method in which specialists and researchers crossed each other in order to look further into the cultural presence of mathematics in society. This study concludes that there is an element of mathematics in the culture of the Sasak tribe, seen from the buildings that have spatial and flat shapes. Other cultures include broad calculations and habits that are integrated with the life of the Sasak people.